Disassembly sequence planning of waste auto parts. (4th May 2021) - Mao, Jia; Hong, Dou; Chen, Zhe; Changhai, Ma; Weiwen, Li; Wang, Ju
ABSTRACT: The disassembly of used products is a critical procedure in remanufacturing, and different disassembly strategies are often obtained from different perspectives. To describe the disassembly process more accurately, the uncertainty of the information in the disassembly process should be considered. Therefore, random variables are introduced for disassembly time, cost, and effort. Based on the extended stochastic Petri net modeling method and stochastic programming theory, a stochastic optimization algorithm combined with artificial intelligence technology and a multiobjective genetic algorithm are designed, and a multiobjective optimization model for the disassembly sequence of used car parts under uncertain conditions is successfully constructed. This model considers the viewpoint of the decision maker. Moreover, the Monte Carlo method is applied to solve the multiobjective optimization model, and the validity and practicability of the model are verified by an example of an automotive transmission. Implications : With the rapid development of the economy and the shortening of the product life cycle, the rate of product renewal is getting faster and faster, which also leads to the production of a large number of waste products. According to the forecast of the relevant departments, it is estimated that, in 2020, there will be about 35 million used televisions, 15 million used refrigerators, 13 million used washing machines, 12 million used air conditioners, 57 million used computers, and 8.3 million scrapped cars. Waste products contain a lot of renewable resources. If they cannot be effectively recycled, it will be a great waste of resources, and unreasonable disposal of waste products may have a negative impact on the environment. Therefore, due to environmental pressure and economic drive, product recycling and remanufacturing activities have caused widespread concern in society. Disassembly is defined as the operation or activity of disassembling an assembly such as a product, assembly, or component, and is the result of multiple removal operations of the product. It is a prerequisite for the efficient recycling of products and the first link in remanufacturing, that is, disassembly as a new production activity, which can provide raw materials for the smooth progress of the remanufacturing production plan, namely, old rough or used parts. Efficient dismantling not only saves natural resources and energy, but also effectively reduces environmental pollution. It is also an important guarantee for promoting the healthy development of the circular economy and achieving sustainable industrial development. The length of time required for the dismantling process, the level of costs, and the amount of profits obtained will directly affect the economic benefits of the recycling of end-of-life products. Therefore, the evaluation and optimization of the dismantling process of waste products have become one of the current hot issues. The research on the dismantling of waste products is conducive to speeding up the recycling process of waste, to a greater extent, the rapid and full recovery of resources, and to a certain extent, it will provide value basis and theoretical significance for subsequent research.